THE MEANING OF TRADITION â€œNJALANGâ€ FOR THE PEOPLE OF MERP AS VILLAGE, MERPAS KAUR REGENCY REGENCY, BENGKULU - Yoka Pradana (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
One of the traditions of grave pilgrimage that is still carried out by the community is the tradition of grave pilgrimage in Merpas Village Kaur Regency, Bengkulu known as Njalang. This tradition is unique be- cause the grave pilgrimage is carried out jointly by villagers every 2nd day of Syawal. This research is aimed at analyzing the meaning of Njalang for the Merpas villagers from the perspective of symbolic interaction. The research method was descriptive qualitative. In-depth interviews and observations of participants were used as the techniques of data collec- tion. The results of this research indicate that the implementation of Njalang tradition is a marriage between cultural activities and religious rituals that have meaning for the people of Merpas village. Njalang is defined as shared reality, as a tradition that creates joint actions and spiri- tual meanings within pilgrims. This article found something new that visiting the tombs of families and religious figures there are several simi- larities as well as differences in meaning. The meaning is emphasized on the implementation of the tradition together.